2024
DOI: 10.1002/aenm.202303381
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Origin of Interface‐Induced High Li and Na Ion Conductivity in Nanocomposite Solid Electrolytes Using X‐Ray Raman Spectroscopy

Laura M. de Kort,
Masoud Lazemi,
Alessandro Longo
et al.

Abstract: Solid‐state electrolytes (SSEs) with high ionic conductivities are crucial for safer and high‐capacity batteries. Interface effects in nanocomposites of SSEs and insulators can lead to profound increases in conductivity. Understanding the composition of the interface is crucial for tuning the conductivity of composite solid electrolytes. Herein, X‐ray Raman Scattering (XRS) spectroscopy is used for the first time to unravel the nature of the interface effects responsible for conductivity enhancements in nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
(153 reference statements)
0
0
0
Order By: Relevance
“…12,14−17 In melt-infiltrated LiBH 4 /(porous) SiO 2 nanocomposites, the formation of Si•••H•••BH 3 complexes and Li + exchange with protons of silanol (SiOH) sites plays a pivotal role in the ionic conductivity increase. 18,19 Nanocomposites of complex metal hydrides and oxides are most commonly prepared via two strategies: ball milling or melt infiltration. Ball milling, or mechanosynthesis, is based on high-energy impacts on the mixture to induce interface contacts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,14−17 In melt-infiltrated LiBH 4 /(porous) SiO 2 nanocomposites, the formation of Si•••H•••BH 3 complexes and Li + exchange with protons of silanol (SiOH) sites plays a pivotal role in the ionic conductivity increase. 18,19 Nanocomposites of complex metal hydrides and oxides are most commonly prepared via two strategies: ball milling or melt infiltration. Ball milling, or mechanosynthesis, is based on high-energy impacts on the mixture to induce interface contacts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A different strategy to increase the room temperature ion conductivity of complex metal hydrides involves the formation of nanocomposites, specifically bringing the hydride in contact with an oxide, such as silica. This approach has been shown to increase the conductivity of LiBH 4 /SiO 2 by at least 3 orders of magnitude at ambient temperatures. , It was revealed that the ion mobility at the interface between the oxide and the metal hydride was greatly enhanced. , In melt-infiltrated LiBH 4 /(porous) SiO 2 nanocomposites, the formation of Si···H···BH 3 complexes and Li + exchange with protons of silanol (SiOH) sites plays a pivotal role in the ionic conductivity increase. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation